A vertical-axis unidirectional rotor for wave energy conversion. (15th July 2018) - Yang, Yingchen; Diaz, Isaiah; Morales, Misael
Abstract: A vertical-axis rotor design for wave energy conversion is discussed in this work. The rotor has a number of cup blades laid out around its shaft. In ocean waves, water particles perform omnidirectional motion. While exposed in waves and driven by omnidirectional flows, the rotor performs unidirectional rotation about its vertically oriented shaft. This rotor concept was tested in a wave flume under various rotor parameters and wave conditions. Results show that the rotor's unidirectional behavior is profound, yet fluctuation of the unidirectional angular velocity broadly exists. A parametric study further revealed relations between the rotor's mean angular velocity and some other parameters. Highlights: A vertical-axis rotor employing cup blades is realized for wave energy conversion. The rotor performs unidirectional rotation about a vertical shaft in waves. The unidirectional angular velocity of the rotor fluctuates in a certain range.